Cooperating, Fast and Slow: Testing the Social Heuristics Hypothesis. - Eirik Strømland; Sigve Tjøtta; Gaute Torsvik (Center for Economic Studies and ifo Institute (CESifo), 2016)
Are humans intuitively cooperative, or do we need to deliberate in order to be generous to others? The Social Heuristics Hypothesis (SHH) proposes that fast instinctive decision making promotes cooperation in social dilemmas. In this paper, we conduct a novel time-pressure experiment to shed light on the cognitive underpinnings of cooperation. Although we find no evidence for a time-pressure effect when considering all subjects, our results, together with a re-analysis of independent data, indicate that a single factor – payoff comprehension – accounts for some studies failure to replicate the finding that fast and intuitive decision making promotes cooperation. Given payoff comprehension, the SHH predicts behavior well. We believe this finding provides a unifying interpretation of the conflicting results in the literature.
Keywords: C72; C91; C92; D03; 330; cooperation; intuition; dual-process; public goods game